Phase 2 study of dasatinib in patients with alveolar soft part sarcoma, chondrosarcoma, chordoma, epithelioid sarcoma, or solitary fibrous tumor. Issue 1 (3rd October 2016) - Schuetze, Scott M.; Bolejack, Vanessa; Choy, Edwin; Ganjoo, Kristen N.; Staddon, Arthur P.; Chow, Warren A.; Tawbi, Hussein A.; Samuels, Brian L.; Patel, Shreyaskumar R.; von Mehren, Margaret; D'Amato, Gina; Leu, Kirsten M.; et al.
Abstract : BACKGROUND: Alveolar soft part sarcoma (ASPS), chondrosarcoma (CS), chordoma, epithelioid sarcoma, and solitary fibrous tumor (SFT) are malignant tumors that are relatively resistant to chemotherapy and for which more effective drug therapy is needed. METHODS: The 5 listed subtypes were enrolled into a single indolent sarcoma cohort in a phase 2 study of dasatinib using a Bayesian continuous monitoring rule for enrollment. The primary objective was to estimate the 6‐month progression‐free survival (PFS) rate according to the Choi criteria with a target of ≥50%. Cross‐sectional imaging was performed before the start of treatment, every 2 months for 6 months, and then every 3 months during treatment. The 2‐ and 5‐year survival rates were determined. RESULTS: One hundred sixteen patients were enrolled within 45 months, and 109 began treatment with dasatinib. The 6‐month PFS rate and the median PFS were 48% and 5.8 months, respectively. The PFS rate at 6 months was highest with ASPS (62%) and lowest with SFT (30%). More than 10% of the patients with ASPS, CS, or chordoma had stable disease for more than 1 year. Collectively, for all 5 subtypes, the 2‐ and 5‐year overall survival rates were 44% and 13%, respectively. An objective response was observed in 18% of the patients with CS or chordoma. CONCLUSIONS: Dasatinib failed to achieve control of sarcoma growth for at least 6 months in more than 50% of the patients in this trial according to the Choi tumor response criteria. An objective tumor response and prolonged stable disease was observed in >10% of patients with CS or chordoma. Cancer 2017;90–97. © 2016 American Cancer Society. Abstract : Dasatinib demonstrates no significant antisarcoma activity in patients with epithelioid sarcoma or solitary fibrous tumor. Patients with alveolar soft part sarcoma have prolonged disease progression–free and overall survival, but this is not necessarily caused by dasatinib. A small minority of patients with chondrosarcoma or chordoma experience an objective tumor response or prolonged stabilization of disease, and this suggests that dasatinib treatment should be further evaluated for these sarcoma subtypes. See also pages 20‐4.